MANAGEMENT OF BURNING MOUTH SYNDROME: A LITERATURE REVIEW - I Nyoman Gede Juwita Putra; Riani Setiadhi (Odonto : Dental Journal, 2019)
Background: Burning mouth syndrome (BMS) is a chronic idiopathic oral dysaesthesia that presents as a burning sensation in the oral cavity usually without any specific oral lesions or laboratory findings. Burning sensations may appear on the buccal mucosa, hard and soft palate, tongue and lips. BMS appears to be more prevalent in postmenopausal women. The term menopause is often used for a condition in which the permanent cessation of the primary function of the ovaries in humans that occurs especially in middle-aged women. Available evidence suggested that BMS is a multifactorial disorder with physiological basis. Pathophysiology of BMS remains unclear. The etiopathogenesis in most patients who complain of burning sensations have interactions with several factors such as local, systemic, and/ or psychogenic factors. The aim of this literature review was to assess and evaluate the management of BMS comprehensively.Discussion: The therapy of BMS including hormone replacement therapy,systemically therapy, such as antidepressants, clonazepam and topical medication (clonidine and capsaicin) and reassurance as the stress management.Conclusion: Proper management of the BMS involves the combination of pharmacologic treatment and psychotherapy, as well as reassurance is an important thing